THE CAPABILITY APPROACH (CA) IN THE EDUCATION OF CHILDREN AND ADULTS WITH DISABILITIES - НЕШИЋ, Невена Б. (Political Review, 2025)
The Capability Approach (CA), developed by economist Amartya Sen, in political philosophy, emphasizes the importance of capabilities, functioning, and freedoms of individuals as necessary components for achieving a good life. The development of the capabilities of individuals is influenced by education, which is key to improving individual well-being and social development. CA is characterized by advocating for social justice, the fight against discrimination, and equal education for all, but in a way that, instead of an exclusive focus on economic progress, emphasizes individual well-being. In education, it prioritizes achieving learning outcomes based on individual capabilities rather than uniform resource allocation or standardized results. In line with these characteristics, this paper was created with the aim of exploring the connection between CA and the education of persons with disabilities, as it highlights the importance of adapting teaching methods, taking into account individual differences and specialized support based on the capabilities of students. By analyzing the content of normative documents and scholarly works dealing with the theoretical framework and application of CA, the paper emphasizes its contribution to the more appropriate implementation of normative frameworks aimed at achieving equality and protecting rights and freedoms in educational policies. This approach is linked to the social model of understanding disability and contrasts with the outdated medical model, which viewed disability as pathology and an individual problem. Emphasizing the importance of environmental factors, the social model includes the engagement of social, political, and educational institutions to improve the physical and mental development and educational capabilities of persons with disabilities according to their own capabilities. Martha Nussbaum, who philosophically developed and expanded CA, advocates for a list of fundamental capabilities for achieving social justice, thus complementing the shortcomings of existing theories of social justice by including the needs of vulnerable groups, such as persons with disabilities. This list includes life, health, bodily integrity, and political participation, aiming to ensure a minimum standard of dignity and freedom for individuals and social groups. Therefore, in inclusive education, it is essential to consider how the social and political climate shapes the perception of disability, human rights, and social welfare, and consequently, how it contributes to the development of capabilities and specialized support, such as personal assistance services, which are essential for inclusive education policy and inclusion in all other areas of social and political life.